A női munka szerepe nemzetközi összehasonlításban - Anna Burgerné Gimes (Hungarian Academy of Sciences, Institute of Economics, 2016)
– In the known history of mankind households dominated the economy. Both food production and industrial activities were carried out mainly in households, first of all by female work. In the early industrial development industrial activities and services have been separated from households in the more developed world. Consequently female occupations were confined to domestic activities and childcare. With the stronger development of industry the demand for workforce has risen. Service sectors have developed, as well. Factories and services needed more and more female workers. Until the end of the nineteenth century few women took part in higher education. With increased attendance at high schools and universities, there have been more women entering in occupations needing secondary- and tertiary-level education. However, few are employed among them on manager and senior official levels. The political empowerment of women is also meager. Female employment has been promoted by the decreasing birthrate as well. Childcare became easier by public service provision, day nurseries, kindergartens, household machines and up to date materials. But the bulk of domestic work is still done by women. According to the European time use surveys women perform between 60 and 66 % of all domestic work. In all the countries men spend more time on gainful work than on domestic tasks on average; however gainful employment and domestic tasks taking together, the daily work of employed women is higher than that of men. Men enjoy more free time than women do. With the decreasing industrial and rising service sector occupation of women and owing to their higher educational level the gender wage gap is diminishing but it still exists. The gender pay gap is particularly large in occupations where the female employment is dominant, as for example in teaching.
Keywords: B54; F50; F66; N00; 330; gender; time use; wage gaps; work